2011
DOI: 10.1016/j.jcta.2010.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic enumeration and limit laws for graphs of fixed genus

Abstract: International audienceIt is shown that the number of labelled graphs with $n$ vertices that can be embedded in the orientable surface $\mathbb{S}_g$ of genus $g$ grows asymptotically like $ c^{(g)}n^{5(g-1)/2-1}\gamma^n n! $, where $c^{(g)} >0$, and $\gamma \approx 27.23$ is the exponential growth rate of planar graphs. This generalizes the result for the planar case $g=0$, obtained by Giménez and Noy. An analogous result for non-orientable surfaces is obtained. In addition, it is proved that several parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 33 publications
4
76
0
1
Order By: Relevance
“…, u h+1 (at most 7 3 n h possibilities, as in the previous proof, since we again need to look for what are now triangulated appearances of K 3 ). Thus, we find that we have built each graph at most 7 3 n h times. Hence, the number of distinct graphs (in S g (n, m)) that we have constructed must be at least |Gn|( αn 2 ) h+1…”
Section: Maximum Degree: Proof Of Theorem 13mentioning
confidence: 98%
See 2 more Smart Citations
“…, u h+1 (at most 7 3 n h possibilities, as in the previous proof, since we again need to look for what are now triangulated appearances of K 3 ). Thus, we find that we have built each graph at most 7 3 n h times. Hence, the number of distinct graphs (in S g (n, m)) that we have constructed must be at least |Gn|( αn 2 ) h+1…”
Section: Maximum Degree: Proof Of Theorem 13mentioning
confidence: 98%
“…. , u a , we now have at most 7 3 n a possibilities instead of n a , since we need to look for what will be triangulated appearances of K 3 (note there are at most n 3 vertex-disjoint triangulated appearances of K 3 , and each can have a vertex in common with at most 6 others, since there are only 6 other triangles touching any triangulated appearance). Hence, we obtain…”
Section: Maximum Degree: Proof Of Theorem 13mentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, as it is shown in [2], see also [1], the number of labelled graphs which can be embedded in a surface of genus satisfies a very similar formula (with the same growth factor). See Table 1 for the asymptotics of these sequences.…”
Section: Introductionmentioning
confidence: 73%
“…Some of the above results were superseded by the results from the recent paper [8], where it is shown that if r = ( holds for almost all . Note that inequality (3) improves (1) for the case of the middle binomial coefficients B because C = S (r) for r = (2), as well as inequality (2) for the case of the Apéry numbers A because A = S (r) for r = (2 2).…”
Section: Introductionmentioning
confidence: 96%